Lower fractional exhaled nitric oxide levels are associated with depressive symptom in males: A population-based cross-sectional study. (November 2020) - Takekawa, Daiki; Kudo, Takashi; Saito, Junichi; Nikaido, Yoshikazu; Sawada, Kaori; Takanashi, Shingo; Hirota, Kazuyoshi
Highlights: It remains uncertain whether both inflammatory markers and fractional exhaled nitric oxide (FeNO) are associated with depression. This cross-sectional study showed that a lower FeNO level was significantly associated with the development of depressive symptoms after adjusting for possible confounding factors. On the other hand, no significant association was found between interleukin (IL)-6 and depressive symptoms or between high-sensitivity C-reactive protein (hs-CRP) and depressive symptoms. Abstract: Background: We examined cross-sectional associations between depression and both inflammatory markers and fractional exhaled nitric oxide (FeNO). Methods: This cross-sectional study is a secondary analysis of the data of the Iwaki Health Promotion Project 2016 (1, 148 subjects). We analyzed the subjects' characteristics and laboratory data including plasma interleukin (IL)-6, high-sensitivity C-reactive protein (hs-CRP), and FeNO. The subjects with Center for Epidemiologic Studies Depression Scale scores ≥16 were assigned to the depression group. We performed a multivariate logistic regression analysis to determine whether inflammatory markers and FeNO were associated with depression. Results: We assessed 1, 099 subjects (430 males, 669 females). The depression group was 237 subjects (21.5%) [84 males (19.5%), 153 females (22.9%)]. The non-depression group was 862 subjects (346 males and 516 females). There were no significant differences in IL-6, hs-CRP, or FeNO between both groups. However, the multivariate logistic regression analysis indicated that lower FeNO was significantly associated with depression in males after adjusting for possible confounding factors (age, BMI, comorbidities, high-sensitivity troponin T, FEV1 %, asthma, antidepressant use, smoker and alcohol drinker) (per 1 bpm increase, OR: 0.982; 95%CI: 0.967–0.998; p  = 0.032). Conclusion: Our findings indicate that lower FeNO may be associated with depression in males.